Production and Potential Income for Business of Oil Palm Empty Fruits Bunch as A Media for Growing Oyster Mushroom - Ni Kadek Sukriasih; Ikawati Karim; Suryani Dewi; Makmur; Cengiz Kayacilar (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
Solid waste produced by oil palm mills consists of oil palm empty bunches, shells, fibers and sludge. Oil palm empty fruit bunches contain 40 percent of cellulose, 24 percent of hemicellulose, 21 percent of lignin, and 15 percent of ash. This study aims to determine the production and the income potential of oyster mushrooms by using oil palm empty fruit bunches as a growth medium. This research is a quantitative descriptive study using an experimental design approach. Analysis of variance showed that all treatments had no significant effect on the length of mycelium fulfillment, the length of the mushroom stalk, the diameter of the fruit cap and the wet weight of the fungus. Treatment with K0 without empty fruit bunches of oil palm has the same growth and production potential as treatment of K1-K4 using oil palm empty fruit bunches. Fungal growth and production are influenced by environmental, nutritional and genetic factors. The potential production of oyster mushrooms with wood sawdust and 15 baglog empty fruit bunches growing media is 5.2 kilograms with a total cost of IDR 297,250. The total revenue for twice harvests for each baglog is IDR 312,000. Therefore, to support the potential for growth and production of oyster mushrooms, oil palm empty fruit bunches can be used as a medium for growing oyster mushrooms because they have the potential for income to be used as a business.